Inter- and Intra-individual Variations in Foveal Outer Nuclear Layer Thickness and Their Associations with Clinical Characteristics in a Healthy Chinese Population - Jia Yu; Lei Li; Chunhui Jiang; Qing Chang; Qi Zhao (Journal of Ophthalmology)
Purpose. To evaluate foveal outer nuclear layer (ONL) thickness and the difference thereof between bilateral eyes and their possible associations with clinical characteristics in a healthy Chinese population. Materials and Methods. Normal subjects were enrolled. Generalized linear models were used to assess the associations of foveal ONL thickness with sex, age, and spherical equivalents (SEs) and the associations of the difference in foveal ONL thickness between bilateral eyes with sex, age, and difference in SEs between bilateral eyes. Results. Totally, 304 subjects were included. The average foveal ONL thickness was 103.19 ± 14.25 (range 70–151) μm in the right eye and 103.90 ± 14.63 (range 69–155) μm in the left eye. The mean difference in foveal ONL thickness between right and left eyes was −0.71 ± 4.36 (range −13 to +12) μm. Men had slightly greater foveal ONL thickness values in both right and left eyes compared with women (both P<0.05); however, some women had a thicker foveal ONL than that of men (85/198 vs. 46/106 in the right eye; 79/198 vs. 52/106in the left eye). Age and SEs were not associated with foveal ONL thickness in either eye (all P>0.05). Sex, age, and difference in SEs between bilateral eyes were not associated with the difference in foveal ONL thickness between bilateral eyes (all P>0.05). Conclusions. Foveal ONL thickness showed wide variation in a normal Chinese population but little difference between bilateral eyes. Both these parameters could not be adjusted by sex, age, SEs, or the SEs difference between bilateral eyes. Thus, in those diseases involving only one eye, the difference or ratio of foveal ONL thickness between the affected eye and normal fellow eye may reflect the actual degree of the disease, rather than the foveal ONL thickness in the affected eye alone.